Homelessness in pregnancy: life course factors and mental health in the context of COVID-19 - Jeffers, Noelene K.; Arno, C. Anneta; McShane, Kelly Sweeney; Vanderpuije, Makeda; Lozano, Andrew; Bradford, Heather M.; Shasanmi-Ellis, Rebecca; Grace, Karen Trister; Robinson, Kelley N.; Marea, Christina X. (Frontiers in Psychiatry, 2025)
IntroductionHomelessness during pregnancy is a significant public health issue in the US that increases the risk of adverse maternal and infant mental and physical health outcomes. The COVID-19 pandemic exacerbated these risks through disruptions in health and social services, employment, and housing stability. Our study aimed to explore how early and cumulative adverse life experiences, mental health challenges, and the pandemic shaped the experience of homelessness during pregnancy.MethodsWe used ​an action-oriented approach for this qualitative exploratory study. We conducted 20 in-depth semi-structured interviews in 2022 among a sample of pregnant, postpartum, and parenting people in Washington DC who experienced homelessness during the COVID-19 pandemic. We conducted a directed content analysis and utilized a life course perspective as the guiding analytic framework.ResultsWe identified six themes: early family instability - childhood through adolescence, vulnerability and conflict as an emerging adult, economic precarity during adulthood, desire for intergenerational family stability and wellbeing, impacts of COVID on homelessness and housing instability for pregnant people, and mental health and housing instability during pregnancy.DiscussionFindings highlight that homelessness during pregnancy reflects cumulative adversity which compound across the life course, with the potential to cause intergenerational consequences for maternal and infant health. Policies that ensure stable, safe housing during the perinatal period, integrated mental health care, and economic supports are urgently needed. We identify critical opportunities for policy and practice reforms, emphasizing the need for trauma-informed solutions using a life-course approach.